The healthy organization - Miller, Eric (Estudios de Administración, 1998)
An explanation is submitted on the concept of healthy organization, its conditioning factors and the consequences thereof. Also, a survey is made of the turbulent environmental conditions faced by organizations today, and of the complexities involved in attempts to turn the work place into a healthy environment. The author point out that nowadays jobs progressively demand a total psychological presence from individuals, which in turn calls for human relations adequate to emotionally hold people, thus constituting a basic factor in the health of organizations. Examples are included, aimed at making the contents clear.